Analisa Perhitungan Penambahan Konstruksi Sekat Dan Dasar Ganda SPOB 3500 DWT Berdasarkan Aturan BKI 2019 - Widodo, Panut (Universitas Ivet, 2021)
Self propelled barge SPOB 3500 DWT carrying Crude Product Oil (CPO) in this study, was built in Singapore in 1984. After operating for a long time, this ship was then included in the Indonesian Classification (BKI), so that in terms of construction it must also follow the requirements of BKI 2019 regulations,. In order to find out the construction adjustments needed to be accepted by the class and also to prevent over-construction, it is necessary to calculate the additional construction based on the latest BKI rules. In this study, an analysis of the old construction drawing data was carried out and mathematical calculation of size of additional transverse bulkhead construction and pelate of double bottom based on rules BKI 2019 Volume. Based on data and regulations of BKI 2019, this ship must add 2 units of transverse bulkhead at cargo tank and change the bottom construction from a single bottom to a double bottom installed along the cargo tank. From the calculation results, it knew that the old bulkhead pelate thickness still meets BKI requirements, the additional transverse bulkhead pelate thickness is 8.0 mm, the double bottom height is 1010 mm and the inner bottom pelate thickness is 8.0 mm.